Silver Nanoparticles Augmented Polycystamine Coated Glassy Carbon Electrodes for Sensitive Sensing of N-Nitrosodimethylamine - Trivedi, Riddhi; Prajapati, Prajesh (Asian Journal of Chemistry, 2026)
Nitrosamine impurities, particularly N-nitrosodimethylamine (NDMA), are potent genotoxic and carcinogenic compounds that can pose significant risks even at trace concentrations. Their occurrence in pharmaceutical products, including cardiovascular, antidiabetic and gastro-retentive drugs, has raised major regulatory concerns, leading to recalls and restrictions on affected products. This study presents an electrochemical sensor for the trace-level detection of NDMA using a polymer-modified glassy carbon electrode (GCE). Silver nanoparticles embedded in polycystamine were integrated onto the GCE surface to enhance the analytical response, sensitivity and selectivity toward NDMA. The electrochemical behavior and quantitative detection of NDMA were investigated using cyclic voltammetry (CV), differential pulse voltammetry (DPV) and square-wave voltammetry (SWV). Surface morphology and modification of the electrode were examined by scanning electron microscopy (SEM). Interference studies were performed to assess the selectivity of the sensor in the presence of potentially coexisting species. The developed silver nanoparticle–polycystamine/GCE platform provides a sensitive and selective electrochemical approach for NDMA detection, with potential application in pharmaceutical quality control and analysis of complex industrial matrices.